Beyond Structured Observation: Methodological Issues and New Directions - Martinko, Mark J.; Gardner, William L. (Academy of Management Review, 1985)
Structured observation studies of managers and supervisors completed before Mintzberg (1068), Mintzberg's work (1968, 1973), and recent contributions are reviewed. Integration of the results of this body of literature reveals several severe limitations with methods currently in use. Methodologies are suggested that complement or build on structured observation as a technique for understanding the nature of managerial work.